Composition of Microplastics Of Coastal Sediments In Kupang and Rote Isalnd, East Nusa Tenggara - Tombus Lucas Anggara; Lintang P. S. Yuliadi; Yudi Nurul Ihsan; M. Rudyansyah Ismail (Journal Omni-Akuatika, 2019)
This research was conducted at the Kupang dan Rote Islands, East Nusa Tenggara in June until November 2018. This research using Wet Peroxide Oxidation methods and aims to obtain data on microplastics distributin that accumulates in coastal sediments in Kupang and Rote Islands.  A result of this research shows that the lowest coast is Ndana Beach at 5 particles/400gr and Pasir Panjang has the highest microplastics abundancre of 23 particles/400gr. A microplastics obtained are fragments, fibers and films but for films that are obtained in 2 stations is Oenggae Beach and Pasir Panjang Beach. A microplastics colors obtained are black, blue, yellow, red, green and white and for sizes small microplastics dominant in all stations. Keywords: Kupang and Rote Island, Microplastic, Coastal Sediments, Wet Peroxide Oxdation